Experiences of Student Teachers in Thailand: A Pre-service Teacher Training Encounter - Tique, Rhoda (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
COVID-19 greatly impacted the lives of students in universities worldwide, more so for the students who are to take their last year of schooling and are about to enter their pre-service teacher training. Students who wished to become teachers before and even during the pandemic needed their pre-service teaching training or teaching internship. It can be done locally or abroad. This study aimed to explore the professional experiences of student teachers while having their pre-service teacher training and on-the-job training abroad. This study aimed to determine the future teachers' professional needs as demonstrated by the challenges experienced by these student teachers, especially in addressing the call of the global community. A qualitative design was used employing individual interviews of the nine (9) Student Teachers participants based on purposive sampling. Then, it was supported by a group interview after the first interview round. Through thematic analysis, the professional experiences of the student teachers were determined and analyzed. Results showed that the student teachers had unique professional experiences, such as dealing with the English level of students, multi-level classroom teaching experience, use of different strategies, professional development, learning the Thai Language, and use of good facilities. The student teachers also faced challenges along with their professional experiences. These are challenges related to the difficulty in teaching English, teaching in multi-level classes, teaching more than the expected class size, multiple co-curricular tasks, and difficulty in learning the Thai language. However, despite these challenges, the student teachers learned and improved themselves in their pre-service teacher training abroad. They managed to equip themselves to become fit regarding the call of Internationalization and Globalization through quality education.